Inaugural speech as a tool of forming speech portrait of the president - Garifullina, Dilyara B.; Khismatullina, Lyutsiya G.; Giniyatullina, Alsu Yu.; Garaeva, Milausha R.; Gimadeeva, Alfiya A. (Linguistics and Culture Review, 2021)
The paper deals with the inaugural speeches of Vladimir Putin (2018) and Donald Trump (2017) and is aimed at analyzing the role of verbal means in forming the speech portraits of political leaders. The article is of urgent interest as it demonstrates the speech portraits of country leaders in relation to national identity, mentality and socio-political course of the country. By means of comparative content analysis we looked for grammatical, lexical and stylistic elements peculiar to a specific linguistic persona while comparing the speeches of the presidents as well as we attempted to determine the specific national backgrounds of political discourse. Thus, each president’s inauguration context model is mostly characterized by a different set of linguistic means. The paper findings may be useful for researchers who deal with interdisciplinary studies, political and cognitive linguistics, political discourse and communication analysis.